Электронные ресурсы отдела книжных памятников и ценных изданий ЦНБ ХНУ имени В. Н. Каразина: открытый доступ для исследований - Журавлева, И.К.; Самохвалова, О.Ю.; Zhuravlyova, I.K.; Samohvalova, O.Yu.; Журавльова, І.К. (Одеський національний університет імені І.І. Мечникова, 2014)
В статье рассмотрены задачи, которые выполняют электронные коллекции редких книг: предоставление широкого доступа читателей к редким и ценным изданиям, обеспечение сохранности оригинала. На примере электронной коллекции Центральной научной библиотеки Харьковского национального университета имени В. Н. Каразина - «eScriptorium: электронный архив редких книг и рукописей для науки и образования» показаны возможности использования полнотекстовых ресурсов ценных изданий. Отражены принципы создания, структура, хронологические рамки, направления, по которым происходит наполнение архива документами. Обрисованы перспективы развития проекта, предоставлены факты сотрудничества с крупнейшими цифровыми библиотеками мира: Всемирной цифровой библиотекой, Европеаной. У статті розглянуті головні завдання, що виконують електронні колекції рідкісних книг: забезпечення збереження оригіналу та надання широкого доступу читачів до рідкісних і цінних видань. Описано приклади цифрових колекцій європейських країн, України та електронної колекції «eScriptorium: Електронний архів рідкісних книг і рукописів для науки та освіти». Відображено принципи створення, структура, хронологічні рамки, напрямки, за якими відбувається наповнення архіву документами. Надаються факти співпраці з найкрупнішими цифровими бібліотеками: Світовою цифровою бібліотекою, Европеаною. The article describes tasks that electronic collections of rare books fulfill: broad access for readers to rare and valuable editions providing, preservation of ensuring of the original. On the example of the electronic collection of the Central Scientific Library of the V. N. Karazin Kharkiv National University - «eScriptorium: electronic archive of rare books and manuscripts for research and education» the possibility of the full-text resources of the valuable editions using is shown. The principles of creation, structure, chronological frameworks, directions of adding the documents to the archive are represented. The perspectives of the project development are outlined as well as examples of the digital libraries of the European countries and Ukraine are provided, the actual task of preserving the originals of the rare books of the country is raised, the innovative approaches to serving users with electronic resources are considered. The evidences of cooperation of the Central Scientific Library of the V.N.Karazin Kharkiv National University with the largest world digital libraries: World Digital Library and Europeana are provided.
Electronic resources of the rare books and valuable editions department of the Central scientific library of the V. N. Karazin Kharkiv national university: open access for research
Zhuravlyova I.К., Director of the Central Scientific Library of V. N. Karazin Kharkiv National University m. Svobody, 4, Kharkiv, 61022, Ukraine. Samohvalova O.Yu., Manager of department of the Central Scientific Library of V. N. Karazin Kharkiv National University. Журавлева И.К., директор Центральной научной библиотеки Харьковского национального университета имени В. Н. Каразина, пл. Свободы 4, Харьков, 61022, Украина тел. +38 (057) 707-52-86, e-mail: cnb@karazin.ua. Самохвалова О.Ю., зав. отделом Центральной научной библиотеки Харьковского национального университета имени В. Н. Каразина, пл. Свободы 4, Харьков, 61022, Украина тел. +38 (057) 707-50-02, e-mail: Olga.J.Samohvalova@univer.kharkov.ua.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::Book and library history; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; eScriptorium; DSpace; электронный архив; электронная коллекция; редкие и ценные издания; доступность фонда; сохранность фонда; цифровые библиотеки; Всемирная цифровая библиотека; Европеана; цифрові бібліотеки; електронні архіві; електронна колекція; рідкісні та цінні видання; доступність фонду; збереження фонду; Всесвітня цифрова бібліотека; digital libraries; electronic archives; electronic collection; rare and valuable editions; manuscripts; fund availability; safety stock; Europeana; the World Digital Library